Peasant communities and Agrarian Reform in Huancavelica - Plasencia Soto, Rommel (2017)
This article across some facts led by the communities of Huancavelica´s department, the struggle for the land during the process of agrarian reform. The temporary line goes from the constitution of the SAIS Huancavelica until 1980, time where Shining Path to burst in the region and it initiates a new chapter in the Andean history.